Insights from the care home staff on the use of observational risk assessment of contractures: Longitudinal evaluation (ORACLE): A qualitative study - Hina Tariq; Kathryn Collins; Joel Dunn; Sam Porter (PLoS ONE, 2025)
Background Contractures are a common but preventable consequence of immobility and inactivity among residents living in care homes. There is a rising prevalence and subsequent impact of contractures on care home residents, leading to the development of a risk assessment tool for contractures, Observational Risk Assessment for Contractures: Longitudinal Evaluation (ORACLE). This qualitative study aims to explore the experience of care staff regarding the usability, acceptability, and practical implementation of ORACLE. Methods A qualitative study using a partly deductive and pragmatic approach was conducted through semi-structured interviews with care home staff in England. The care staff members were selected via purposive sampling and were interviewed either through videoconferencing or in person in a private room at care homes. The interviews were recorded and transcribed verbatim. The data collected was coded using NVivo and synthesised using thematic analysis. Results Ten care staff members were interviewed from five care homes (four senior staff members and six healthcare assistants). Three overarching themes were identified: 1) usability of ORACLE, 2) acceptability of ORACLE and 3) contextual factors that can potentially influence the practical implementation of ORACLE in a care home setting. Respondents found the tool to be user-friendly and well-integrated within existing care routines. The study also identified factors relating to care home processes, the people involved, the training environment, and the policy context that tend to support or inhibit the effective implementation of ORACLE. Conclusion The study offers preliminary insights into the usability and acceptability of ORACLE and its application in a care home setting.